Pengetahuan Sikap dan Perilaku Masyarakat dalam Penggunaan Jamban Sehat Di Kelurahan Sumpang Minangae Kecamatan Bacukiki Barat Kota Parepare - Agusman Adam; Usman Usman; Makhrajani Majid (Media Literasi Indonesia, 2025)
Knowledge of Attitudes and Behaviors of Society in the Use of Healthy Latrines. Healthy Latrines a building used for a place to dispose of feces that must be owned by the community, especially such as in Sumpang Minangae Village for example. Because feces is one of the big problems that can cause disease. This type of research is descriptive intending to show and tell events that occur in the field using random sampling techniques. The purpose of the study is to add to the public's insight into the importance of family latrines and attitudes, actions and the development of community behavior towards the use of family latrines. From the results of this study on people's attitudes and behaviors in the use of healthy latrines, I can conclude, public knowledge (51. 2%), positive community attitudes (70. 7 %), postive community behavior (75. 6%), positive government roles (68. 3%). As for the advice from the Puskesmas more especially for the head of puskesmas in terms of sanitarian to be more effective in counseling about clean and healthy living behavior (PHBS), Especially regarding healthy health care and also more to the Government to be more assertive to provide policies or rules regarding defecation on the beach. and it is expected to the local government to regulate and maintain and supervise the cleanliness of the surrounding environment.